Faktor - Faktor yang Berhubungan dengan Pelaksanaan Triase - Gervasius Nong Sensi; Yanny Trisyani W; Aan Nuraeni (Jurnal Keperawatan Silampari, 2023)
This study aims to determine what factors influence the implementation of triage in the Emergency Unit. This research method uses a literature review conducted with PRISMA guidance and electronic databases, namely Google Scholar, Pubmed, and Science Direct, with the keywords "Accuracy, " "Affecting, " "Decision Making, " "Emergency Department, "AND " Triage." The results obtained were 12 full-text articles, using Indonesian and English, and publications in the 2020 - 2023 range. The results of a literature review of the reviewed articles found that four factors had the most significant influence on the implementation of triage in the Emergency Unit: aspects of workload, motivation, work experience, and knowledge of nurses in the Emergency Unit. In conclusion, the accuracy of triage implementation is essential in determining patient care priorities based on the level of emergency so that it does not cause death or disability in patients. This literature review found that factors such as workload, motivation, experience, and knowledge of nurses greatly influence the implementation of triage in the Emergency Unit. Keywords: Workload, Motivation, Experience, Knowledge